Design of Collecting and Loading System for Tapered Roller Bearings - Balsa, Péter; Bodzás, Sándor (International Journal of Engineering and Management Sciences, 2016)
My assignment was to design a new machine that would serve as a centerpiece of the package & assembly line, will collect the assembled bearings and place them in closed storage and dispenses them as necessary .